206k views
2 votes
If a, b, c are all non -zero and a+b+c= 0, prove a²÷ bc +b²÷ ac +c²÷ ab =3

User Tjjjohnson
by
5.8k points

2 Answers

5 votes

Please find attached photograph for your answer

If a, b, c are all non -zero and a+b+c= 0, prove a²÷ bc +b²÷ ac +c²÷ ab =3-example-1
User Viggo
by
5.9k points
4 votes

Combining the fractions gives


(a^2)/(bc)+(b^2)/(ac)+(c^2)/(ab)=(a^3+b^3+c^3)/(abc)

Since
a+b+c=0, we also have


(a+b+c)^3=0


a^3+b^3+c^3+3a^2b+3a^2c+3ab^2+3b^2c+3ac^2+3bc^2+6abc=0

If we add and subtract the last 7 terms of the left hand side to/from the numerator, we get


((a+b+c)^3-(3a^2b+3a^2c+3ab^2+3b^2c+3ac^2+3bc^2+6abc))/(abc)


=-3(a^2b+a^2c+ab^2+b^2c+ac^2+bc^2+2abc)/(abc)


=-3((a+b)(a+c)(b+c))/(abc)

Also because
a+b+c=0, we have


\begin{cases}a=-(b+c)\\b=-(a+c)\\c=-(a+b)\end{cases}

so we find that


-3((a+b)(a+c)(b+c))/(abc)=-3((-c)(-b)(-a))/(abc)=3(abc)/(abc)=3

User Dmitrii Dovgopolyi
by
6.0k points